Diversity Of Local Tree Species In Faruhumpenai Nature Reserve, East Luwu - Andi Utami Batari Putri; Witno Witno; Hadijah Aziz Karim; Hilarius Kamis (Universitas Andi Djemma Palopo, 2024)
Faruhumpenai nature reserve as one of the largest nature reserves in Sulawesi that holds high biodiversity that has the potential to be maintained. One of the potential flora that exists is the local tree species. The presence of local trees in the faruhumpenai nature reserve has so far not been studied in depth. So the purpose of this study is to find out the diversity of local tree species in the Faruhumpenai Nature Reserve. Data collection uses an exploratory method with a traced path. The number of paths created is as many as 5 paths with a length of 200 meters each. The results of this study obtained data on 50 types of local trees from 31 families. One of the families with the most species is the family Lauraceae with 4 species are Cinnamomum Sp, Cryptocarya Sp, Litsea Mappacea Boert and Litsea Noronhae. However the species that dominates each path is Dyospiros Celebica (ebony) which had The highest INP value. Line 1 (37,26%), line 2 (23,06%), line 3 (38,77%), line 4 (33,81%) and line 5 (20,77%). The value of species diversity (H') is included in the medium-high category with a value (2.90-3.23).